Interferon-α before allogeneic bone marrow Ttransplantation in chronic myelogenous leukemia does not affect outcome adversely, provided it is discontinued at least 90 days before the procedure - Hehlmann, Rüdiger; Hochhaus, Andreas; Kolb, Hans-Jochem; Hasford, Jörg; Gratwohl, Alois; Heimpel, Hermann; Siegert, Wolfgang; Finke, Jürgen; Ehninger, Gerhard; Holler, Ernst; Berger, Ute; Pfirrmann, Markus; et al. (Blood, 1999)
The influence of interferon- (IFN) pretreatment on the outcome after allogeneic bone marrow transplantation (BMT) in chronic myelogenous leukemia (CML) is controversial. One goal of the German randomized CML Studies I and II, which compare IFN ± chemotherapy versus chemotherapy alone, was the analysis of whether treatment with IFN as compared to chemotherapy had an influence on the outcome after BMT. One hundred ninety-seven (23%) of 856 Ph/bcr-abl-positive CML patients were transplanted. One hundred fifty-two patients transplanted in first chronic phase were analyzed: 86 had received IFN, 46 hydroxyurea, and 20 busulfan. Forty-eight patients (32%) had received transplants from unrelated donors. Median observation time after BMT was 4.7 (0.7 to 13.5) years. IFN and chemotherapy cohorts were compared with regard to transplantation risks, duration of treatments, interval from discontinuation of pretransplant treatment to BMT, conditioning therapy, graft-versus-host disease prophylaxis and risk profiles at diagnosis and transplantation, and IFN cohorts also with regard to performance and resistance to IFN. Outcome of patients receiving related or unrelated transplants pretreated with IFN, hydroxyurea, or busulfan was not significantly different. Five-year survival after transplantation was 58% for all patients (57% for IFN, 60% for hydroxyurea and busulfan patients). The outcome within the IFN group was not different by duration of prior IFN therapy more or less than 5 months, 1 year, or 2 years. In contrast, a different impact was observed in IFN-pretreated patients depending on the time of discontinuation of IFN before transplantation. Five-year survival was 46% for the 50 patients who received IFN within the last 90 days before BMT and 71% for the 36 patients who did not (P = .0057). Total IFN dosage had no impact on survival after BMT. We conclude that outcome after BMT is not compromised by pretreatment with IFN if it is discontinued at least 3 months before transplantation. Clear candidates for early transplantation should not be pretreated with IFN.